PENGARUH PEMBELAJARAN MENGGUNAKAN VIRTUAL LABORATORY TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI GELOMBANG - Kansil, Monica J.; Warouw, Zusje W. M; Harahap, Fransiska (LPPM Politeknik Saint Paul Sorong, 2024)
This study aims to determine the influence of learning using virtual laboratories on students' critical thinking skills on wave materials. The research was conducted at SMP Negeri 6 Tondano, Academic Year 2023-2024. This study uses a Quasi Experiment consisting of 2 classes, namely the Experiment class with 15 students and the control class with 16 students. The results of this study showed that there was a difference in the results of the critical thinking ability of the experimental class that was treated using virtual laboratory-assisted learning media and the control class using conventional methods. This difference can be seen from the average results of the post-test critical thinking ability of the experimental class that has been given learning using the virtual laboratory is 70.67 while the pre-test of the control class that uses conventional learning is 45.63. This is also evident from the results of the t-test calculation which produced a value of .